Self‐Assembly of Wireframe DNA Nanostructures from Junction Motifs. Issue 35 (24th July 2019) - Huang, Kai; Yang, Donglei; Tan, Zhenyu; Chen, Silian; Xiang, Ye; Mi, Yongli; Mao, Chengde; Wei, Bryan
Abstract: Wireframe frameworks have been investigated for the construction of complex nanostructures from a scaffolded DNA origami approach; however, a similar framework is yet to be fully explored in a scaffold‐free "LEGO" approach. Herein, we describe a general design scheme to construct wireframe DNA nanostructures entirely from short synthetic strands. A typical edge of the resulting structures in this study is composed of two parallel duplexes with crossovers on both ends, and three, four, or five edges radiate out from a certain vertex. By using such a self‐assembly scheme, we produced planar lattices and polyhedral objects. Abstract : Conjunction junction, what's your function? Junction motifs of specific angle arrangements are designed. 2D wireframe lattices and 3D wireframe polyhedra are constructed accordingly.